PENGARUH TRANSFORMATIONAL LEADERSHIP TERHADAP INNOVATIVE WORK BEHAVIOR : MEDIASI PSYCHOLOGICAL EMPOWERMENT DAN MODERASI TASK COMPLEXITY PADA BPJS KETENAGAKERJAAN WILAYAH JAWA TENGAH & DIY: (THE EFFECT OF TRANSFORMATIONAL LEADERSHIP ON INNOVATIVE WORK BEHAVIOR: THE MEDIATING ROLE OF PSYCHOLOGICAL EMPOWERMENT AND THE MODERATING ROLE OF TASK COMPLEXITY AT BPJS KETENAGAKERJAAN IN THE CENTRAL JAVA & YOGYAKARTA REGION) - Khairunnisa, Shafira; Tristanto Laksana Putra, Juni; Munandari, Dhealelia; Putri, Rizky Atika Salsabila Ivabianca (e-Journal Ekonomi Bisnis dan Akuntansi, 2026)
This study aims to determine transformational leadership on innovative work behavior mediated by psychological empowerment and moderated by task complexity. Thisstudy uses a quantitative approach with the analysis technique used is partial least squares with 156 employee respondents in the membership sector at BPJS Ketenagakerjaan throughout Central Java and DIY. The dependent variable used is innovative work behavior, the independent variable is transformational leadership, the mediating variable is psychological empowerment, and the moderating variable is task complexity. The results of the study show that transformational leadership and psychological empowerment affect innovative work behavior among employees with positive and significant results. Transformational leadership shows positive and significant results on innovative work behavior mediated by psychological empowerment. Task complexity showsthat it can moderate transformational leadership on innovative work behavior.